AB0071 THERAPEUTIC EFFECTS OF BONE MARROW MESENCHYMAL STEM CELLS-DERIVED EXOSOMES ON OSTEOARTHRITIS. (2nd June 2020) - Dong, C.; Liu, Y.; Deng, A.; Ji, J.; Zheng, W.; Gu, Z.
Abstract : Background: Mesenchymal stem cells (MSCs) have shown chondroprotective effects in clinical models of osteoarthritis (OA) [1] . Objectives: The study aimed to investigate the therapeutic potential of exosomes from human bone marrow MSCs (BM-MSCs) in alleviating OA. Methods: The anterior cruciate ligament transection (ACLT) anddestabilization of the medial meniscus (DMM) surgery were performed on the knee joints of a rat OA model, followed by intra-articular injection of BM-MSCs or their exosomes. The beneficial effects were evaluated by histological staining, OARSI scores and micro-CT. Furthermore, BM-MSCs-derived exosomes were administrated to primary human chondrocytes to observe the functional and molecular alterations. In addition, lncRNA MEG3 were investigated in chondrocytes to explore the biological contents accounting for anti-OA effects of BM-MSCs-derived exosomes. Results: Based on the observation in the rat OA model, both of BM-MSCs and BM-MSCs-derived exosomes alleviated cartilage destruction, reduced joint damage and restored the trabecular bone of OA rats. In addition, in vitro assays showed that BM-MSCs- exosomes could maintain the chondrocyte phenotype by increasing collagen type II synthesis and inhibiting IL-1β- induced senescence and apoptosis. Furthermore, exosomal lncRNA MEG3 also reduced the senescence and apoptosis of chondrocytes induced by IL-1β, indicating that lncRNA MEG3 might partially account for the anti-OA effects of BM-MSC exosomes. Conclusion: The exosomes from BM-MSCs exerted beneficial therapeutic effects on OA by reducing the senescence and apoptosis of chondrocytes, suggesting that MSCs-derived exosomes might provide a candidate therapy for OA treatment. References: [1]Mckinney J M, Doan T N, Wang L, et al. Therapeutic efficacy of intra-articular delivery of encapsulated human mesenchymal stem cells on early stage osteoarthritis[J]. Eur Cell Mater, 2019, 37: 42-59. Disclosure of Interests: None declared